Notes on the Evolution of a Research Community: Organization Studies in Anglophone North America, 1945–2000 - Augier, Mie; March, James G.; Sullivan, Bilian Ni (Organization Science, 2005)
Since the Second World War, the field of organizations studies has grown substantially in the number of researchers, number of publications, and amount of research produced. It has moved from being a combination of established disciplines to becoming a quasi-discipline of its own, with its own journals and professional associations. It has established a standardized set of ancestors, a stylized history. It has solidified an academic home in business schools. This history has implications for understanding both the future of organizations research and the social dynamics of the development of scholarly communities.